LA CARIDAD CONTRA LA CIENCIA. UNA LUCHA IDEOLÓGICA ENTRE LA SOCIEDAD DE BENEFICENCIA DE LIMA CONTRA LA FACULTAD DE MEDICINA DE SAN FERNANDO, EN LA SEGUNDA MITAD DEL SIGLO XIX - Coello Rodríguez, Antonio (2015)
This article explains the struggle between the Charity Society of Lima led by small elite against the Faculty of Medicine of San Fernando, Lima, represented by a body of doctors. The Faculty of Medicine of San Fernando, was trying to organize and lead a hygienist policy to develop in Lima, while trying to take control of the hospitals, thus to implement the scientific advances that were being developed in countries of the old-world. Also doctors believing themselves as the new “enlightened” of the republic, express their points of views on various issues of daily life as well as on policy. On the other hand, the Charity Society of Lima, in charge of directing and ensure the care of hospitals, saying they were able to organize and manage hospital aid, for which they even brought The Sisters of Charity, from Chile to be in charge of the pharmacies of hospitals in Lima . Facing this dichotomy, doctors and the Charity Society expressed their opinions, in printed media (newspapers, magazines and annual reports).